Effectiveness and uptake of screening programmes for coronary heart disease and diabetes: a realist review of design components used in interventions. Issue 11 (7th November 2013) - Holland, Carol; Cooper, Yvonne; Shaw, Rachel; Pattison, Helen; Cooke, Richard
Abstract : Objective: To evaluate behavioural components and strategies associated with increased uptake and effectiveness of screening for coronary heart disease and diabetes with an implementation science focus. Design: Realist review. Data sources: PubMed, Web of Knowledge, Cochrane Database of Systematic Reviews, Cochrane Controlled Trials Register and reference chaining. Searches limited to English language studies published since 1990. Eligibility criteria: Eligible studies evaluated interventions designed to increase the uptake of cardiovascular disease (CVD) and diabetes screening and examined behavioural and/or strategic designs. Studies were excluded if they evaluated changes in risk factors or cost-effectiveness only. Results: In 12 eligible studies, several different intervention designs and evidence-based strategies were evaluated. Salient themes were effects of feedback on behaviour change or benefits of health dialogues over simple feedback. Studies provide mixed evidence about the benefits of these intervention constituents, which are suggested to be situation and design specific, broadly supporting their use, but highlighting concerns about the fidelity of intervention delivery, raising implementation science issues. Three studies examined the effects of informed choice or loss versus gain frame invitations, finding no effect on screening uptake but highlighting opportunistic screening as being more successful for recruiting higher CVD and diabetes risk patients than an invitation letter, with no differences in outcomes once recruited. Two studies examined differences between attenders and non-attenders, finding higher risk factors among non-attenders and higher diagnosed CVD and diabetes among those who later dropped out of longitudinal studies. Conclusions: If the risk and prevalence of these diseases are to be reduced, interventions must take into account what we know about effective health behaviour change mechanisms, monitor delivery by trained professionals and examine the possibility of tailoring programmes according to contexts such as risk level to reach those most in need. Further research is needed to determine the best strategies for lifelong approaches to screening.